KAJIAN KEBIJAKAN PENGAWASAN MUTU BARANG EKSPOR HASIL PERTANIAN - Bagas Haryotejo; Yudi Fadilah (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2009)
The increase in competitiveness level of the agricultural product export is associated with the ability to fulfil quality requirement from the export destination country, which becomes more stringent than before. Facts on the field reveal that the awarness level regarding quality product from the farmers/producers, intermediate trader, and exporter still low. In order to prevent the occurrence of subtsandar quality product from Indonesia and to maintain potential market for Indonesia’s export products. Minister of Industry and trade has issued Ministerial Decree on the Standarization. Certification, Acreditation and Quality Control at the Ministry of Trade (Sk. Menperindag No. 108/MPP/Kep/5/1996) and Ministerial Decree on Mandatory Quality Control for Specific Ekspor Products (Sk Menperindag No. 164/MPP/KEP/6/1996), and its implementation regulation, the Secretary General of Ministry of Industry and Trade Decree No. 470/SJ/SK/VII/1996 on the Provisions and Procedures on the Quality Control for Specific Eksport Products. This research aims to identify problems in quality control for export products from regulation and implementation aspects. From regulation point of view, the research found that from the regulation aspect, the legal foundation regarding quality control for export products is no long valid. While from the implementation aspect, is it noted that the quality control activites were not conducted properly. Aside from that, there are no specifics criterias applied in determining export goods/products that must be take into quality control regime. This condition has led to pro and contra amongst the business entity. Therefore the formulation of the set criterias that can be used to determine/select comodities need to be put into quality control. The criterias are: (1) the quality control management infrastructure; (2) aquired SNI; (3) take into consideration Farmers’ability; (4) the comparative advantages; (5) the compliace to export destination country requirements and; (6) the existence of quality complaint mechanism from importer countries. It is also the current legal foundation on the regulations for products quality control and its substance needs to be revised in due time.